Visual impairment and its associated factors among the adult population of Kuala Pajam Village, Branang, Selangor, Malaysia. - Rozhan SMR; Halim I; Shamsul Azhar Shah (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : Visual impairment among the rural community has rarely been studied in this country. The purpose of this study is to determine the prevalence of visual impairment and its related factors among the adult population of Kampung Kuala Pajam, Branang. Methodology : A cross sectional study was carried out in Kampung Kuala Pajam, Mukim Beranang from 25th of December till 30th of December 2007. Universal sampling is adopted and the sample size consists of 321 respondents who is 18 years and above. Trained interviewer has been used to obtain the data through questionnaire and eye examinations using logMAR chart, Red Reflex eye test, Relative Afferent Pupillary Defect (RAPD) test and Pin-Hole test. Result : A total of 261 respondents who fulfil the criteria were interviewed and had eyes examination during the study period. The prevalence of visual impairment in this population was 9.2% and factors that showed significant association were age (p <0.001, r2 +0.542), education level (p <0.001), employment status (p 0.027), income (p <0.001, r2 -0.303), hypertension (p <0.001), refractive eye problem (p<0.001) and media eye problem (p=0.002). The risk of developing visual impairment were OR=5.168 (CI: 1.035-25.797) among the low education group, OR=23.172 (CI: 5.956-90.150) among media eye problem group and OR=3.150 (CI: 1.060-9.368) among refractive eye problem group. Conclusion : Improving knowledge and awareness among the adult population in this community through health promotion programme emphasizing on healthy lifestyle, symptoms of systemic diseases and eye care by the Health District Office and Community Health Clinic together with committed cooperation of the Head Villagers will have a long term effect in reducing the prevalence of visual impairment.